DEKONSTRUKSI STEREOTIP MASKULIN IKLAN PRODUK KOSMETIK DALAM VIDEO IKLAN MS GLOW FOR MAN #SEMUAJUGABISA - Mutiara, Destita (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
Advertising through the media as a constructor has a great influence on public thinking. Advertising can create a new view of meaning in social reality, including cosmetic advertising. The meaning of handsome in cosmetic advertisements described by advertisers who has become an identity formed by the community. In the case of advertisements for cosmetic products, the meaning of beauty is only related to the physical. The object of this study is the MS Glow for Man advertisement that played by Marshell Widianto X Babe Cabiita through Youtube videos. It is qualitative research with descriptive analytic, to see and analyze the deconstruction and courage of advertisements in deconstructing and creating unusual advertisements. The approach that used is the semiotic approach of Roland Barthes, an analysis of two signs, to see the signs and ideologies that are displayed through advertisements and Derrida's analysis to deconstruct the meaning of masculine and handsome by strengthening #SemuaJugaBisa to see that all can see the same rights for the label of handsome as well as the glow offered by the product. So, the deconstruction is not all the handsome are stocky and white. There is no difference between one man and another in the advertisement.